ChemInform Abstract: Catalytic anti‐Markovnikov Hydrobromination of Alkynes. Issue 40 (30th September 2014) - Uehling, Mycah R.; Rucker, Richard P.; Lalic, Gojko
Abstract The first catalytic method for anti‐Markovnikov hydrobromination of alkynes is developed.